Evaluation of Peritoneal Dialysis Complications and Survival of Patients; A Single Center Study, Yazd ,Iran - K Parandeh (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2008)
Introduction: Peritoneal dialysis is an established form of renal replacement therapy used in many patients with end – stage renal disease . Peritoneal dialysis has different complications This study was conducted in order to evaluate its complications and different survival probabilities of factors in Shahid Rahnemoon hospital . Methods: In this retrospective, historical cohort study, reports of 161 patients on peritoneal dialysis (Shaheed Rahnemoon hospital, dialysis department) from 3.Dec.1997 to 20.May.2007 were evaluated. Required data was gathered and analyzed by specific statistical tests. Results: The mean age of patients was 49.37 years (2 to 88 years) and most of them (41.6%) included in 40-59 years age group category. Peritonitis, exit site infection and catheter malposition was seen in 41.6% , 6.8% and 9.3% of patients ,respectively.Rate of peritonitis in females was more than males (p=0.002). Diabetes mellitus had no effect on death rate, but hypertension had a protective role. Conclusion: Peritonitis ,exit site infection and catheter malposition is more prevalent in females, but mortality rate is significantly higher in males.